ADSORPTION OF Mg(II) AND Ca(II) ON DISULFONATO-SILICA HYBRID - Choiril Azmiyawati; Nuryono Nuryono; Narsito Narsito (Indonesian Journal of Chemistry, 2012)
Adsorption of Mg(II) and Ca(II) on disulfonato-silica hybrid (DSSH) in the aqueous solution has been studied. The hybrid was synthesized by sol-gel process with sodium silicate solution from rice hull ash, chloroprophyltrimethoxysilane (CTS) and 4-amino-5-hydroxy-naphtalene-2,7-disulfonic acid monosodium salt (ANSNa) as silica source, cross linker and active group, respectively. Sodium silicate solution was reacted with CTS and ANSNa that were added dropwise. Adsorption of magnesium and calcium ions on DSSH was carried out in a batch system. Solution pH significantly affected magnesium and calcium adsorption and the optimum condition was obtained at pH = 6. The synthesized DSSH showed a high adsorption capacity of 0.0844 mmol/g and 0.1442 mmol/g for Mg(II) and Ca(II), respectively. The adsorption isotherm obtained with Langmuir isotherm model gives the negative values of ΔG°, i.e. -23.334 kJ/mol and -22.757 kJ/mol for Mg(II) and Ca(II), respectively, indicating the spontaneous process of adsorption. Kinetic studies showed that the adsorption of Mg(II) and Ca(II) ions onto HDSS follows the pseudo-second-order kinetics.